2018
DOI: 10.1590/1678-7757-2018-0088
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of salivary immunoglobulin A with Body Mass Index and fat percentage in overweight/obese children

Abstract: Obesity is considered a risk factor for periodontal health due to the low- grade inflammation promoted by the increased adipose tissue. Objective: This study aimed to determine correlations and associations between gingival inflammation (Simplified Oral Hygiene Index, and Gingival Index), salivary immunoglobulin A (s-IgA), and salivary parameters (salivary flow and osmolality) in normal-weight and overweight/obese children. Material and Methods: Ninety-one children, aged 6 to 12 years old (8.6±1.9 years), were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Pandey et al observed that immunoglobulin A (IgA‐s), which binds to different molecular components and interferes with microbial adhesion, is predominant in saliva and is an important part in caries prevention process. A previous study showed that overweight/obese children have higher levels of saliva IgA‐s . Given the above, it is reasonable to infer that OW children have fewer chances to develop dental caries because their saliva contains higher levels of IgA‐s.…”
Section: Discussionmentioning
confidence: 95%
“…Pandey et al observed that immunoglobulin A (IgA‐s), which binds to different molecular components and interferes with microbial adhesion, is predominant in saliva and is an important part in caries prevention process. A previous study showed that overweight/obese children have higher levels of saliva IgA‐s . Given the above, it is reasonable to infer that OW children have fewer chances to develop dental caries because their saliva contains higher levels of IgA‐s.…”
Section: Discussionmentioning
confidence: 95%
“…The review included 12 cross-sectional studies [ [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] ] and three prospective cohort studies [ [40] , [41] , [42] ]. The included studies were conducted in 10 countries: Brazil [ 33 , 36 , 40 ], Sweden [ 32 , 34 , 38 ], the United States [ 30 , 35 ], Canada [ 31 ], China [ 39 ], Kuwait [ 42 ], Poland [ 37 ], Saudi Arabia [ 28 ], Switzerland [ 41 ], and Turkey [ 29 ]. Except for two studies that did not provide information on the sex of the participants [ 28 , 39 ], all remaining studies included children and adolescents of both sexes.…”
Section: Resultsmentioning
confidence: 99%
“…There were also significantly higher salivary concentrations of IL-6, TNF-α, insulin, and MCP-1 (monocyte chemoattractant protein-1) in these patients. The leptin concentration was also directly proportional to the insulin concentration [39]. Furthermore Perez et al demonstrated that the concentration of salivary IgA (s-IgA) is significantly higher in the group of overweight and obese children than in the group of normal weight children, reaching the highest concentration among obese children (p < 0.05) having body fat content expressed as percentage of total body composition (p < 0.05) [40].…”
Section: Discussionmentioning
confidence: 99%
“…There were also significantly higher salivary concentrations of IL-6, TNF-a, insulin, and MCP-1 (monocyte chemoattractant protein-1) in these patients. The leptin concentration was also directly proportional to the insulin concentration [ 39 ]. Furthermore Perez et al .…”
Section: Discussionmentioning
confidence: 99%